Biomass delignification with green solvents towards lignin valorisation: ionic liquids vs deep eutectic solvents - da Costa Lopes, André M. (2021)
The use of renewable resources as feedstocks to ensure the production of goods and commodities for society has been explored in the last decades to switch off the overexploited and pollutant fossil-based economy. Today there is a strong movement to set bioeconomy as priority, but there are still challenges and technical limitations that must be overcome in the first place, particularly on biomass fractionation. For biomass to be an appellative raw material, an efficient and sustainable separation of its major components must be achieved. On the other hand, the technology development for biomass valorisation must follow green chemistry practices towards ecofriendly processes, otherwise no environmental leverage over traditional petrochemical technologies will be acquired. In this context, the application of green solvents, such as ionic liquids (ILs) and deep eutectic solvents (DES), in biomass fractionation is envisaged as promising technology that encompasses not only efficiency and environmental benefits, but also selectivity, which is a crucial demand to undertake cascade processes at biorefinery level. In particular, this article briefly discusses the disruptive achievements upon the application of ILs and DES in biomass delignification step towards an effective and selective separation of lignin from polysaccharides. The different physicochemical properties of these solvents, their interactions with lignin and their delignification capacity will be scrutinized, while some highlights will be given to the important characteristics of isolated lignin fractions for further valorisation. The advantages and disadvantages between ILs and DES in biomass delignification will be contrasted as well along the article.